CRITICAL THEMES IN SOUTH AFRICA'S FOREIGN POLICY: AN OVERVIEW (The Strategic Review for Southern Africa, 2020)
This article represents a synthetic overview of the key themes which have animated scholarly research in South Africa's foreign policy over the last two decades. These themes will be addressed and are situated against the broad contextual background of important philosophical challenges, transitional developments, and managerial dilemmas during the formative presidential periods of Mandela and Mbeki. This context provides the analytical parameters for the focus on six themes which arguably shape debates and thinking about the conduct of South Africa's foreign policy, namely: the institutional dynamics at the level of the state; the multilateral and global agenda; trade and economic diplomacy; the peace, security, and mediation dimension; the donor and development assistance role; and the scourge of xenophobia. These themes will continue to exercise a profound influence on the collective endeavour of South Africa's foreign policy community to sustain its standing as a middle-power with soft power assets that is able to shape African and global agendas. Arising from these thematic considerations, some concluding thoughts highlight on-going normative, substantive, and policy challenges for the Zuma administration.
Keywords: South Africa's foreign policy; philosophical challenges; transitional developments; managerial dilemmas; presidential periods; Mandela; Mbeki; institutional dynamics at the level of the state; the multilateral and global agenda; trade and economic diplomacy; peace, security, and mediation dimension; donor and development assistance role; scourge of xenophobia; Zuma administration